(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
This study was conducted to investigate the pollution level of heavy metals such as Pb, Cr, Ni, Mn, Zn and Fe in the water, sediment and body organs (head, intestine & tile) of Tilapia zilli and Clarias batrachus from River Rukubi Doma, Nasarawa State. This was carried out using Atomic Absorption Spectrophotometer. Magnesium was the most highly concentrated in the various matrices. Metal levels in the various body organs of the two fishes studied were found to be highly concentrated in the head. Comparison of metal levels in the body parts of the two fishes, sediment and water showed that Cu (85.9%) had the widest variability while Mg (13.1%) was the least. Also comparison of metal levels in the body parts of the Tilapia zilli and Clarias batrachus showed that Mg has the highest mean metal concentration in Clarias batrachus (655.85 µgg-1) than in Tilapia zilli (608.40 µgg-1). Iron showed the highest mean metal concentration in Tilapia zilli (166.51 µgg-1) than in Clarias batrachus (57.20 µgg-1). The heavy metals determined were mostly within the ranged of acceptable limit with exception of Pb, Cr and Mn. In view of this study it is recommended that biological monitoring of fishes meant for consumption from this water body be carried out regularly to ensure human safety. This study contributes to understanding the evaluation of metals level in fishes and their importance in food balanced approach for essential benefits.